Speed Synchronization of Multi-Conveyor System Using Bidirectional Interaction Topologies - Bima Sakti Putra Ardi; Agung Prayitno; Veronica Indrawati (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2026)
Long production lines composed of multiple stand-alone mode controllers often face challenges when speed synchronization is required, as each setpoint must be manually adjusted one by one. The issue can be addressed by designating one conveyor as the leader, while the others operate as followers that continuously adjust their speeds to match the leader. The main objective of this study is to develop a multi-conveyor leader–follower system based on distributed cooperative control, allowing all follower conveyors to maintain synchronized speeds with the designated leader unit. In this setup, the leader is equipped with the ability to command all followers to align their speeds to its own, which is governed by a fuzzy logic controller (FLC). Each follower operates in one of two modes: a stand-alone FLC mode or a synchronization mode using cooperative control. The cooperative control mechanism relies on speed information shared among neighboring conveyors, as defined by the system topology. Two types of bidirectional interaction topologies are explored in this work: The Bidirectional Coordinated Conveyor Topology (BCCT) and the Bidirectional Leader Coordinated Conveyor Topology (BLCCT). The proposed control strategy was tested on a mini multi-conveyor setup with one leader and four followers. Synchronization tests on two topologies produced RMSE values of 30.88 RPM for BCCT and 43.87 RPM for BLCCT. A brief disturbance was also applied to one follower to assess the controller’s resilience and its effect on overall system coordination. The study confirms that combining fuzzy logic with cooperative control enhances synchronization and coordination across conveyors.